2018
DOI: 10.4236/jcc.2018.61008
|View full text |Cite
|
Sign up to set email alerts
|

Individual Identification Using ECG SignalsW

Abstract: The electrocardiogram (ECG) signal used for diagnosis and patient monitoring, has recently emerged as a biometric recognition tool. Indeed, ECG signal changes from one person to another according to health status, heart geometry and anatomy among other factors. This paper forms a comparative study between different identification techniques and their performances. Previous works in this field referred to methodologies implementing either set of fiducial or set non-fiducial features. In this study we show a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The matching score is defined between 0% and 100% (with 100% being impossible to be realized). (c) Identification/recognition: It involves determining the identity of an unknown subject from a database of individuals [120]. Notably, the biometric system can then either attribute the identity corresponding to the most matching characterization found in the database…”
Section: ) General Scheme Of Ecg-based Biometric Systemmentioning
confidence: 99%
“…The matching score is defined between 0% and 100% (with 100% being impossible to be realized). (c) Identification/recognition: It involves determining the identity of an unknown subject from a database of individuals [120]. Notably, the biometric system can then either attribute the identity corresponding to the most matching characterization found in the database…”
Section: ) General Scheme Of Ecg-based Biometric Systemmentioning
confidence: 99%
“…Accordingly, the accuracy in Tantawi et al (2012) is indistinct while there is no testing for the unauthorized persons Yarong & Gang (2015), Gawande & Ladhake (2015) and Bassiouni et al (2016). Diab et al (2018) show how many subjects are used in testing authorized and unauthorized subjects.…”
Section: Figure 1 Enrolment Verification and Identification Processesmentioning
confidence: 99%
“…The accuracy of the identification system is 100%. Diab et al (2018) suggested an identification system based on ECG signal. This work forms a comparative study between different identification techniques and their performances.…”
Section: Related Workmentioning
confidence: 99%
“…Non-fiducial features are obtained by using several methods from the transformed domain. These features needless computation time than the fiducial features also it doesn't require to find boundaries of the ECG waveforms which change constantly [7][8][9]. Two ECG approaches are available based on the used features which are fiducial and non-fiducial approaches as shown in Figure 3.…”
Section: Introductionmentioning
confidence: 99%